A Comprehensive Biophysical Model of Ion and Water Transport in Plant Roots. I. Clarifying the Roles of Endodermal Barriers in the Salt Stress Response - Foster, Kylie J.; Miklavcic, Stanley J. (Frontiers in Plant Science, 2017)
In this paper we present a detailed and comprehensive mathematical model of active and passive ion and water transport in plant roots. Two key features of this model are the explicit consideration of the separate, but interconnected, apoplastic and symplastic transport pathways for ions and water, and the inclusion of both active and passive ion transport. We have applied this model to investigate the respective roles of the endodermal Casparian strip and suberin lamellae in the salt stress response of plant roots. While it is thought that these barriers influence different transport pathways, it has proven difficult to distinguish their separate functions experimentally. In particular, the specific effect of the suberin lamellae has been unclear. A key finding based on our simulations was that the Casparian strip is essential in preventing excessive uptake of Na$^+$ into the plant via apoplastic bypass, with a barrier efficiency that is reflected by a sharp gradient in the steady-state radial distribution of apoplastic Na$^+$ across the barrier. Even more significantly, this function of the Casparian strip cannot be replaced by the action of membrane transporters. The simulations also demonstrated that the positive effect of the Casparian strip, in terms of controlled Na$^+$ uptake, was somewhat offset by its contribution to the osmotic stress component: a more effective Casparian strip increased the detrimental osmotic stress effect. In contrast, the suberin lamellae were found to play a relatively minor, even non-essential, role in the overall response to salt stress, with the presence of the suberin lamellae resulting in only a slight reduction in Na$^+$ uptake. However, perhaps more significantly, the simulations identified a possible function of the suberin lamellae which has not previously been considered. Specifically, the lamellae reduced plant energy requirements by acting as a physical barrier to prevent the passive leakage of Na$^+$ into the endodermal cells. The model results suggest that more and particular experimental attention should be paid to the character of the Casparian strip present when assessing the salt tolerance abilities of different plant varieties and species. Indeed, the Casparian strip appears to be a more promising target for plant breeding